THE RELATIONSHIP OF ACADEMIC STRESS AND EATING DISORDERS WITH NUTRITIONAL STATUS AMONG FINAL-YEAR STUDENTS AT UNIVERSITAS PENDIDIKAN INDONESIA - Salma Almira Kuswihandono; Isti Kumalasari; Muchamad Rizki Sentani; Delita Septia Rosdiana (Jurnal Gizi dan Pangan Soedirman, 2026)
Final-year students often face academic pressure that may increase stress, disturb sleep quality, and alter dietary patterns, which can ultimately affect nutritional status. This study aimed to examine the relationship between sleep quality, academic stress, food consumption levels, and eating disorder tendencies with the nutritional status of final-year students at Universitas Pendidikan Indonesia. This research employed a quantitative approach with a cross-sectional design and was analyzed using the Spearman correlation test. A total of 105 students were selected through proportionate stratified random sampling. Data were collected using the PSQI questionnaire, SLSI, EDDS, 1×24-hour dietary recall, and interviews. The results showed significant relationships between academic stress (p=0.032) and bulimia nervosa tendencies (p=0.016) with the nutritional status of final-year students. In contrast, no significant relationships were found between nutritional status and sleep quality, dietary intake, general eating disorder tendencies, or anorexia nervosa. In conclusion, this study demonstrated weak associations between academic stress and bulimia nervosa tendencies with the nutritional status of final-year students.